Mechanistic investigation on up and down conversion of Er3+ and Gd3+ co-doped YTiNbO6 phosphors. Issue 115 (3rd November 2015) - Yu, Zhichao; Zhou, Guangjun; Zhou, Juan; Zhou, Haifeng; Kong, Peng; Wu, Yaqiang; Huang, Huining; Yu, Xiaoqiang; Zhang, Xingshuang; Zhang, Ruoyao
Abstract : The present work focuses on the up and down conversion of YNbTiO6 with different quenching concentrations of Er 3+ and Gd 3+ as well as the energy transfer processes. Abstract : YTiNbO6 phosphors doped with Er 3+, Gd 3+ were synthesized via a facile sol–gel and combustion approach. The crystal structure and particle morphology were characterized and the phonon energy was investigated in detail. The up-conversion emission excited at 980 nm and down-conversion emission excited at 378 nm of Er 3+ with different concentrations were analysed. They both have strong green emission peaks at 522 and 552 nm but the red emission peak at 668 nm only appears in the up-conversion. Furthermore, the Er 3+ quenching concentration for up-conversion is higher than that for down-conversion because the up-conversion is a complex multiple stepwise process which includes energy transfer, phonon-assisted energy transfer and excited state absorption that can cover a wider range of Er 3+ doping concentrations. Moreover, the influence of co-doped Gd 3+ on the morphology and particle size was also explored. Gd 3+ had a great effect on the up and down conversion emission intensity as well as the decay time of up-conversion by changing the structure distortion, vibration frequencies and surface defects.